a Asymptotic behavior of the sum of sines series in the zero neighborh - Solodov А.П. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2018)
t: The work is devoted to the refinement of the asymptotics of the sum of a series in sines with convex, slowly varying coefficients, obtained by S. Alancic, R. Boyanic and M. Tomich [1] and enhanced by S.A. Telyakovsky [2] and A. Yu. Popov [